The adventures of Tom Sawyer [large type] - Twain, Mark, 1835-1910 (Thorndike classics., 2006)
Mark Twain's first novel about Huck Finn and Tom Sawyer is a fond reminiscence of life in Hannibal, Missouri, an evocation of Mark Twain's own boyhood along the banks of the Mississippi during the 1840s. "Most of the adventures recorded in this book really occurred," he tells us. This is a book one never forgets: Tom whitewashing Aunt Polly's fence, Tom and Huck's dreadful oath, their cure for warts ("spunk water" and dead cats), Tom's puppy love for Becky Thatcher, the boys playing "pirate" on Jackson's Island.--